Efficient MAC Protocols for Wireless Sensor Networks Endowed with Directive Antennas: A Cross-Layer Solution - Gianfranco Manes; Romano Fantacci; Francesco Chiti; Michele Ciabatti; Giovanni Collodi; Davide Di Palma; Ilaria Nelli; Antonio Manes (EURASIP Journal on Wireless Communications and Networking, 2007)
This paper deals with a novel MAC layer protocol, namely, directive synchronous transmission asynchronous reception (D-STAR) able to space-time synchronize a wireless sensor network (WSN). To this end, D-STAR integrates directional antennas within the communications framework, while taking into account both sleep/active states, according to a cross-layer design. After characterizing the D-STAR protocol in terms of functional characteristics, the related performance is presented, in terms of network lifetime gain, setup latency, and collision probability. It has shown a remarkable gain in terms of energy consumption reduction with respect to the basic approach endowed with omnidirectional antennas, without increasing the signaling overhead nor affecting the setup latency.